Recent Advances in Tungsten-Oxide-Based Materials and Their Applications - Wu, Chang-Mou; Naseem, Saba; Chou, Min-Hui; Wang, Jyun-Hong; Jian, Ying-Qi (Frontiers in Materials, 2019)
Among several active photothermal nanomaterials, tungsten-oxide-based materials have received considerable attention recently because of their ability to absorb near-infrared (NIR) light and their efficient light-to-heat conversion properties. In addition, tungsten-oxide-based materials have an unusual oxygen defect structure and strong local surface plasma resonance (LSPR), which offers strong photoabsorption in a broad wavelength range of the NIR region. In the past, several light-absorbing nanomaterials such as noble metals, polymeric materials, and other inorganic nanomaterials were of interest for their use in photothermal therapy for cancer treatment. In this study, we review the synthesis, properties, and applications of tungsten-oxide-based nanomaterials as a new type of photothermal material. The basic ideas behind photothermal nanomaterial development as well as the factors that influence their structural designs are also discussed in this study. In addition, recent progress in various fields such as NIR light-shielding, pyroelectric, water evaporation, photocatalysis, gas sensors, and energy-related applications for WO3-x- and MxWO3-based nanomaterials (including their hybrids) are highlighted. Finally, this review presents promising insights into this rapidly growing field that may inspire additional research leading to practical applications.